The role of selected tools of institutionalising the environmental area in the process of generating the environmental performance - Sikacz, Hanna; Teneta-Skwiercz, Dorota (Rola wybranych narzędzi instytucjonalizacji obszaru środowiskowego w procesie generowania efektów działalności środowiskowej, 2022)
The article is a part of a stream of research related to environmental, social and governance (ESG) aspects of business activity, focusing on environmental factors. Its main objective is to identify the strength of the relation between selected tools of institutionalising the environmental area and the environmental performance a the company. Six tools were analysed: Policy Emissions, Policy Water Efficiency, Policy Energy Efficiency, Policy Sustainable Packaging, Policy Environmental Supply Chain and Environment Management Team. ESG data of companies from the clothing sector obtained from the Refinitiv database were used for the research, which found that the most popular policy is Policy Energy Efficiency, and the least popular, Policy Sustainable Packaging. There is a positive correlation between the tools of institutionalisation of the environmental area and Environmental Score. Policy Emissions, Environment Management Team, and Policy Water Efficiency, are most correlated with environmental performance and should be of particular interest to companies. This research makes an important contribution to the discussion on the effectiveness of tools for institutionalising the environmental area within a company.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 115-133
Keywords: clothing industry; sustainability; environmental score; environmental policy; Environmental Management System; przemysł odzieżowy; zrównoważony rozwój; polityka środowiskowa; zespół zarządzania środowiskiem